A wear-resistant car body protective coating and preparation method thereof
Through specific ratio raw material components and high-temperature ball milling and other processes, wear-resistant body protective coatings with improved hardness and adhesion are prepared, which solves the problems of insufficient hardness and poor adhesion of traditional polyurethane paint films, and achieves higher wear resistance and corrosion resistance.
Patent Information
- Application Number
- CN202411220102.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-02
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-09-02
AI Technical Summary
Traditional polyurethane paint films have problems such as insufficient hardness and poor adhesion in the automotive coating field, which leads to easy damage and peeling, making it difficult to meet the market's demand for improving the performance of automotive protective coatings.
Using a specific ratio of raw material components, including polyisocyanate, second polymer polyol, modified wear-resistant filler and pearled slurry, abrasive body protective coating with improved hardness and adhesion is prepared through high-temperature ball milling and amidation reactions.
It significantly improves the hardness and adhesion of the coating, enhances wear resistance and mechanical properties, reduces the contact opportunity between corrosive media and metal substrates, and has good corrosion resistance.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of coatings, and in particular to a wear-resistant vehicle body protective coating and a preparation method thereof. Background Art
[0002] In the automotive industry, the application of protective coatings is particularly important to improve the durability and appearance of vehicles. Traditional polyurethane paint films have been widely used in the field of automotive coatings due to their excellent flexibility, chemical resistance and moderate UV resistance. However, as the market's expectations for the performance of automotive protective coatings continue to increase, some limitations of traditional polyurethane paint films have begun to emerge, such as insufficient hardness leading to easy damage, and weak adhesion and easy peeling.
[0003] The hardness of a polyurethane paint film is directly related to its ability to resist physical damage. Paint films with lower hardness are more likely to be scratched when they encounter minor collisions or abrasions, which not only damages the appearance but also shortens the service life. In addition, the adhesion between the paint film and the vehicle body substrate is one of the key factors in evaluating the quality of the coating. Weak adhesion will cause the paint film to peel off during use, especially when cleaning or facing complex road conditions. In order to solve these problems, technicians have tried to add wear-resistant fillers to protective coatings, but existing fillers are often poorly dispersed in the coating, which may lead to a decrease in the mechanical properties of the paint film.
[0004] Therefore, the present invention prepares a wear-resistant vehicle body protective coating. Summary of the invention
[0005] The purpose of the present invention is to provide a wear-resistant vehicle body protective coating and a preparation method thereof, so as to solve the problems existing in the prior art.
[0006] In order to solve the above technical problems, the present invention provides the following technical solutions: a wear-resistant car body protective coating, wherein the raw material components include, by weight, 100 parts by weight of component A, 87-88 parts by weight of component B, 6-8 parts by weight of modified wear-resistant filler, 23.5 parts by weight of pearlescent slurry, 15-17 parts by weight of solvent, 0.2-0.3 parts by weight of defoamer, 0.8-1.2 parts by weight of leveling agent, and 1.4-1.6 parts by weight of anti-settling agent; the component A includes, by weight, 36-37 parts by weight of polyisocyanate, 24-25 parts by weight of a first polymer polyol, and 37-39 parts by weight of a diluent; the component B includes, by weight, 32-33 parts by weight of a second polymer polyol, 6-7 parts by weight of a chain extender, and 0.0002-0.0004 parts by weight of a catalyst.
[0007] Furthermore, the polyisocyanate is hexamethylene diisocyanate or hexamethylene diisocyanate trimer;
[0008] The first polymer polyol is polytetramethylene ether diol; the chain extender is 1,4-butanediol; the catalyst is dibutyltin dilaurate; the defoamer is BYK-141; the leveling agent is BYK-306; and the anti-settling agent is BYK-410.
[0009] Furthermore, the modified wear-resistant filler is obtained by modifying copper-magnesium-aluminum hydrotalcite with silane coupling agent KH560 and tetraethylenepentamine in sequence.
[0010] Furthermore, the pearlescent slurry comprises, by weight, 10 parts by weight of butyl acetate, 12 parts by weight of pearlescent powder pigment, and 1.5 parts by weight of acrylic dispersant.
[0011] Furthermore, the second polymer polyol is a polyether polyol modified by 2-ethynylaniline.
[0012] The present invention also provides a method for preparing a wear-resistant vehicle body protective coating, comprising the following preparation steps:
[0013] (1) preparing the ingredients according to the aforementioned raw material components and proportions;
[0014] (2) 23.5 parts by weight of pearlescent slurry, 15-17 parts by weight of solvent, and 6-8 parts by weight of modified wear-resistant filler were mixed, heated to 150° C. and ball-milled for 4 h, then 87-88 parts by weight of component B were added, the temperature was further raised to 180-200° C., ball-milled for 6 h, and cooled to room temperature to obtain a primary mixture;
[0015] (3) Add 100 parts by weight of component A to the primary mixture, add 0.2-0.3 parts by weight of defoamer, 0.8-1.2 parts by weight of leveling agent, and 1.4-1.6 parts by weight of anti-settling agent after ball milling for 6 hours, continue ball milling for 1-3 hours, and let stand for 8 minutes to obtain a wear-resistant body protective coating.
[0016] Furthermore, the preparation method of the pearlescent slurry is as follows:
[0017] Under stirring at 200-400 rpm, 12 parts by mass of pearlescent pigment were added to 7 parts by mass of butyl acetate, followed by adding 1.5 parts by mass of acrylic dispersant and 3 parts by mass of butyl acetate, and stirring was continued for 20-40 minutes to obtain a pearlescent slurry.
[0018] Furthermore, the preparation method of the modified wear-resistant filler is as follows:
[0019] 10 parts by weight of copper-magnesium-aluminum hydrotalcite are added to 400 parts by weight of a 2 mol / L hydrochloric acid solution, refluxed at 80°C, stirred for 12 hours, repeatedly centrifugally washed, dried at 70°C, ground and sieved, then added to 300 parts by weight of anhydrous ethanol, and then 30-40 parts by weight of silane coupling agent KH560 are added, refluxed at 90°C under a nitrogen atmosphere, stirred for 24 hours, repeatedly centrifugally washed with anhydrous ethanol for 2-4 times, vacuum dried at 70°C, ground and sieved, continued to be added to 400 parts by weight of anhydrous ethanol, and then 20-30 parts by weight of tetraethylene pentamine are added, refluxed at 90°C under a nitrogen atmosphere, stirred for 24 hours, repeatedly centrifugally washed with anhydrous ethanol for 2-4 times, vacuum dried at 70°C, and ground and sieved to obtain a modified wear-resistant filler.
[0020] Furthermore, the preparation method of component B is as follows:
[0021] Mix 32-33 parts by mass of the second polymer polyol, 6-7 parts by mass of the chain extender, and 0.0002-0.0004 parts by mass of the catalyst, dehydrate under vacuum at 100-110°C and -0.1 MPa for 2-3 hours, cool and pour into a ball mill for dispersion for 6 hours, discharge, seal and set aside to obtain component B.
[0022] Furthermore, the preparation method of the second polymer polyol is as follows:
[0023] 4-ethynylbenzoic acid, polyether polyol, cyclohexane and concentrated sulfuric acid are mixed and shaken, then zeolite is added and heated to reflux at 85°C for 1.8 to 2.2 hours, wherein the mass ratio of 4-ethynylbenzoic acid, cyclohexane and concentrated sulfuric acid is 3:3 to 4:1, and the molar ratio of the carboxyl group in 4-ethynylbenzoic acid to the hydroxyl group in the polyether polyol is 1:4 to 6, to obtain 4-ethynylbenzoic acid modified polyether polyol; a mixed solution of 2-ammonium iodide, bis(triphenylphosphine)palladium chloride, cuprous iodide, triphenylphosphine, acetonitrile and triethylamine is stirred and dissolved, and then 4-ethynylbenzoic acid modified polyether polyol is added, and nitrogen is kept The mixture is stirred and refluxed at 100° C. for 16 to 18 hours under protection, poured into water, extracted with ethyl acetate, and the organic phase is washed with saturated brine and dried with anhydrous magnesium sulfate to obtain a second polymer polyol; wherein the mass ratio of 2-ammonium iodide, bis(triphenylphosphine)palladium chloride, cuprous iodide, triphenylphosphine, and 4-ethynylbenzoic acid modified polyether polyol is 1:0.05:0.05:0.05:1.1 to 1.3; the mass ratio of the mixed solution of 2-ammonium iodide, acetonitrile and triethylamine is 1:400 to 600; the volume ratio of acetonitrile to triethylamine in the mixed solution of acetonitrile and triethylamine is 5:1.
[0024] Furthermore, the preparation method of component A is as follows: 36 to 37 parts by mass of polyisocyanate are mixed with 37 to 39 parts of diluent, the temperature is raised to 75°C, 24 to 25 parts by mass of the first polymer polyol are added dropwise under stirring, the addition is completed within 40 minutes, the temperature is raised to 75 to 85°C, and the reaction is carried out at a constant temperature for 1.5 hours. At this time, the content of isocyanate groups is 6% to 7%, the temperature is lowered to 60°C, and vacuum degassing is carried out for 30 minutes to obtain component A.
[0025] Compared with the prior art, the beneficial effects achieved by the present invention are:
[0026] The wear-resistant vehicle body protective coating of the present invention comprises, by weight, 100 parts by weight of component A, 87-88 parts by weight of component B, 6-8 parts by weight of modified wear-resistant filler, 23.5 parts by weight of pearlescent slurry, 15-17 parts by weight of solvent, 0.2-0.3 parts by weight of defoamer, 0.8-1.2 parts by weight of leveling agent, and 1.4-1.6 parts by weight of anti-settling agent; the component A comprises, by weight, 36-37 parts by weight of polyisocyanate, 24-25 parts by weight of first polymer The invention discloses a novel nanostructured ...
[0027] The present invention adopts a polyurethane elastomer prepared from component A and component B as the base resin of the coating. Compared with traditional PVC olefin and asphalt-based coatings, the polyurethane has better abrasion resistance and elasticity, is easier to construct, and has better smoothness. Among them, the second polymer polyol adopts 2-ethynylaniline-modified polyether polyol, and a rigid benzene ring is introduced into the flexible polyether polyol chain, thereby enhancing the hardness and thermal stability of the wear-resistant car body protective coating.
[0028] The modified wear-resistant filler of the present invention is obtained by sequentially modifying copper-magnesium-aluminum hydrotalcite with silane coupling agent KH560 and tetraethylenepentamine, and tetraethylenepentamine is grafted on the surface of the copper-magnesium-aluminum hydrotalcite to enhance the dispersibility of the copper-magnesium-aluminum hydrotalcite in component B, thereby enhancing the wear resistance and mechanical properties of the wear-resistant vehicle body protective coating.
[0029] When preparing the wear-resistant vehicle body protective coating, the present invention first mixes pearlescent slurry, modified wear-resistant filler and component B; on the one hand, the pearlescent slurry and the modified wear-resistant filler are pre-dispersed in component B to increase the dispersibility of the pearlescent slurry and the modified wear-resistant filler in the wear-resistant vehicle body protective coating, thereby enhancing the wear resistance and mechanical properties of the wear-resistant vehicle body protective coating; on the other hand, the carboxyl group in the acrylic dispersant in the pearlescent slurry and the tetraethylenepentamine on the surface of the modified wear-resistant filler undergo an amidation reaction, and undergo cyclization at 180-190° C. to form imidazoline; at the same time, the 2-ethynylaniline in component B undergoes an intramolecular cyclization reaction under the catalytic action of copper-magnesium-aluminum hydrotalcite to form indole, and the imidazoline and indole can form coordination bonds with the surface of the metal substrate, thereby forming a protective film, reducing the chance of contact between the corrosive medium and the metal substrate, and enabling the wear-resistant vehicle body protective coating to have corrosion resistance. DETAILED DESCRIPTION
[0030] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0031] In order to more clearly illustrate the method provided by the present invention, the following examples are used to describe in detail the various index testing methods of the wear-resistant vehicle body protective coating prepared in the following examples are as follows:
[0032] Adhesion test: The adhesion of the paint film was tested according to the standard GB / T 9286-1998; 80-mesh sandpaper was used to polish the tinplate (size 120 mm×50 mm×0.28 mm), and after cleaning with alcohol and drying, the wear-resistant body protective coating prepared in the embodiment and the comparative example was sprayed to prepare samples, and left at room temperature for one week, and then tested; a paint film grid was used to draw a uniform grid on the paint film; then transparent tape was used to stick to the grid and pressed hard to ensure that there were no bubbles, and then the tape was quickly torn off, the damage result of the grid was observed, and compared with the standard to determine the adhesion of the paint film; the test was repeated three times to ensure the experimental error.
[0033] Hardness test: The hardness of the paint film was tested according to the standard GB / T 6739-2022; 80-mesh sandpaper was used to polish the tinplate (size 120 mm×50 mm×0.28 mm), and after cleaning with alcohol and drying, the wear-resistant body protective coating prepared in the embodiment and the comparative example was sprayed to prepare a sample, and placed at room temperature for one week, and then tested; a pencil was placed in a trolley pencil hardness tester, and the trolley pencil hardness tester was pushed to make the pencil draw a line greater than 7 mm on the surface of the paint film, and the hardness was tested in order from high to low, and the damage of the paint film was observed. The experiment was repeated five times, and the maximum hardness without exposing the bottom was recorded as the paint film hardness.
[0034] Corrosion resistance: The neutral salt spray resistance of the paint film was tested according to the standard GB / T 1771-2007; a cold-rolled steel plate with a size of 120 mm × 50 mm × 0.5 mm was polished with 80-mesh sandpaper, cleaned with alcohol, sprayed with the wear-resistant body protective coating prepared in the embodiment and the comparative example to prepare a sample, and placed at room temperature for one week before testing; the steel plate was sealed with plastic tape before testing, and then the sample was placed in a salt spray box, and the corrosion degree of the sample was observed every 12 hours, and then put back to its original place after observation.
[0035] Flexibility: The flexibility of the paint film was tested according to the standard GB / T 6742-2007; 80-mesh sandpaper was used to polish the tinplate (size: 120 mm × 50 mm × 0.28 mm), cleaned with alcohol and dried, and then the wear-resistant body protective coating prepared in the embodiment and the comparative example was sprayed to prepare samples, and placed at room temperature for one week, and then tested; the test plate was placed with the paint film surface facing up, close to a fixed shaft rod, and then bent around the shaft rod, and then the paint film damage was observed, and the minimum diameter of the shaft rod that did not cause paint film damage was recorded, and the experiment was repeated three times.
[0036] Some of the raw materials used in the examples and comparative examples of the present invention are as follows:
[0037] The defoamer is BYK-141;
[0038] The leveling agent is BYK-306;
[0039] The anti-settling agent is BYK-410;
[0040] The polyisocyanate is hexamethylene diisocyanate;
[0041] The first polymer polyol is polytetramethylene ether glycol;
[0042] The chain extender is 1,4-butanediol;
[0043] The catalyst is dibutyltin dilaurate;
[0044] The diluent is prepared by mixing xylene and butyl acetate in a mass ratio of 2:3;
[0045] The solvent is obtained by mixing xylene, butyl acetate and N-methylpyrrolidone in a mass ratio of 1:1:3;
[0046] Example 1
[0047] A method for preparing a wear-resistant vehicle body protective coating comprises the following preparation steps:
[0048] (1) The following raw material components and proportions are prepared: 100 parts by mass of component A, 87 parts by mass of component B, 6 parts by mass of modified wear-resistant filler, 23.5 parts by mass of pearlescent slurry, 15 parts by mass of solvent, 0.2 parts by mass of defoamer, 0.8 parts by mass of leveling agent, and 1.4 parts by mass of anti-settling agent;
[0049] (2) 23.5 parts by weight of pearlescent slurry, 15 parts by weight of solvent, and 6 parts by weight of modified wear-resistant filler were mixed, heated to 150° C. and ball-milled for 4 h, then 87 parts by weight of component B were added, the temperature was further raised to 180° C., ball-milled for 6 h, and cooled to room temperature to obtain a primary mixture;
[0050] (3) Add 100 parts by weight of component A to the primary mixture, add 0.2 parts by weight of defoamer, 0.8 parts by weight of leveling agent, and 1.4 parts by weight of anti-settling agent after ball milling for 6 hours, continue ball milling for 1 hour, and let stand for 8 minutes to obtain a wear-resistant body protective coating.
[0051] The preparation method of the pearlescent slurry is as follows:
[0052] Under stirring at 200 rpm, 12 parts by mass of pearlescent pigment were added to 7 parts by mass of butyl acetate, followed by the addition of 1.5 parts by mass of acrylic dispersant and 3 parts by mass of butyl acetate, and stirring was continued for 20 minutes to obtain a pearlescent slurry.
[0053] The preparation method of the modified wear-resistant filler is as follows:
[0054] 10 parts by mass of copper-magnesium-aluminum hydrotalcite are added to 400 parts by mass of a hydrochloric acid solution with a concentration of 2 mol / L, refluxed at 80°C, stirred for 12 hours, repeatedly centrifuged and washed with water, dried at 70°C, ground and sieved, then added to 300 parts by mass of anhydrous ethanol, and then 30 parts by mass of silane coupling agent KH560 are added, refluxed at 90°C under a nitrogen atmosphere, stirred for 24 hours, repeatedly centrifuged and washed twice with anhydrous ethanol, vacuum dried at 70°C, ground and sieved, continued to be added to 400 parts by mass of anhydrous ethanol, and then 20 parts by mass of tetraethylene pentamine were added, refluxed at 90°C under a nitrogen atmosphere, stirred for 24 hours, repeatedly centrifuged and washed twice with anhydrous ethanol, vacuum dried at 70°C, and ground and sieved to obtain a modified wear-resistant filler.
[0055] The preparation method of component B is as follows:
[0056] 32 parts by mass of the second polymer polyol, 6 parts by mass of the chain extender and 0.0002 parts by mass of the catalyst were mixed, vacuum dehydrated at 100°C and -0.1 MPa for 2 hours, cooled and poured into a ball mill for dispersion for 6 hours, discharged, sealed and set aside to obtain component B.
[0057] The preparation method of the second polymer polyol is as follows:
[0058] 4-ethynylbenzoic acid, polyether polyol, cyclohexane and concentrated sulfuric acid were mixed and shaken well, then zeolite was added and heated to reflux at 85°C for 1.8h, wherein the mass ratio of 4-ethynylbenzoic acid, cyclohexane and concentrated sulfuric acid was 3:3:1, and the molar ratio of the carboxyl group in 4-ethynylbenzoic acid to the hydroxyl group in polyether polyol was 1:4, to obtain 4-ethynylbenzoic acid modified polyether polyol; 2-ammonium iodide, bis(triphenylphosphine)palladium chloride, cuprous iodide, triphenylphosphine, acetonitrile and triethylamine were stirred and dissolved, and then 4-ethynylbenzoic acid modified polyether polyol was added, and nitrogen The mixture was stirred and refluxed at 100°C for 16 hours under gas protection, poured into water, extracted with ethyl acetate, and the organic phase was washed with saturated brine and dried with anhydrous magnesium sulfate to obtain a second polymer polyol; wherein the mass ratio of 2-ammonium iodide, bis(triphenylphosphine)palladium chloride, cuprous iodide, triphenylphosphine, and 4-ethynylbenzoic acid modified polyether polyol was 1:0.05:0.05:0.05:1.1; the mass ratio of the mixed solution of 2-ammonium iodide, acetonitrile and triethylamine was 1:400; the volume ratio of acetonitrile and triethylamine in the mixed solution of acetonitrile and triethylamine was 5:1.
[0059] The preparation method of component A is as follows: 36 parts by mass of polyisocyanate and 37 parts of diluent are mixed, the temperature is raised to 75° C., 24 parts by mass of the first polymer polyol are added dropwise under stirring, the addition is completed within 40 minutes, the temperature is raised to 75° C., and the reaction is carried out at a constant temperature for 1.5 hours. At this time, the content of isocyanate groups is 6%, the temperature is lowered to 60° C., and vacuum degassing is carried out for 30 minutes to obtain component A.
[0060] Example 2
[0061] A method for preparing a wear-resistant vehicle body protective coating comprises the following preparation steps:
[0062] (1) The following raw material components and proportions are prepared: 100 parts by mass of component A, 87.5 parts by mass of component B, 7 parts by mass of modified wear-resistant filler, 23.5 parts by mass of pearlescent slurry, 16 parts by mass of solvent, 0.25 parts by mass of defoamer, 1 part of leveling agent, and 1.5 parts by mass of anti-settling agent;
[0063] (2) 23.5 parts by weight of pearlescent slurry, 16 parts by weight of solvent, and 7 parts by weight of modified wear-resistant filler were mixed, heated to 150° C. and ball-milled for 4 h, then 87.5 parts by weight of component B were added, the temperature was further raised to 190° C., ball-milled for 6 h, and cooled to room temperature to obtain a primary mixture;
[0064] (3) Add 100 parts by mass of component A to the primary mixture, add 0.25 parts by mass of defoamer, 1 part of leveling agent, and 1.5 parts by mass of anti-settling agent after ball milling for 6 hours, continue ball milling for 2 hours, and let stand for 8 minutes to obtain a wear-resistant body protective coating.
[0065] The preparation method of the pearlescent slurry is as follows:
[0066] Under stirring at 300 rpm, 12 parts by mass of pearlescent pigment were added to 7 parts by mass of butyl acetate, followed by the addition of 1.5 parts by mass of acrylic dispersant and 3 parts by mass of butyl acetate, and stirring was continued for 30 minutes to obtain a pearlescent slurry.
[0067] The preparation method of the modified wear-resistant filler is as follows:
[0068] 10 parts by mass of copper-magnesium-aluminum hydrotalcite are added to 400 parts by mass of a hydrochloric acid solution with a concentration of 2 mol / L, refluxed at 80°C, stirred for 12 hours, repeatedly centrifuged and washed with water, dried at 70°C, ground and sieved, then added to 300 parts by mass of anhydrous ethanol, and then 35 parts by mass of silane coupling agent KH560 are added, refluxed at 90°C under a nitrogen atmosphere, stirred for 24 hours, repeatedly centrifuged and washed with anhydrous ethanol for 3 times, vacuum dried at 70°C, ground and sieved, continued to be added to 400 parts by mass of anhydrous ethanol, and then 25 parts by mass of tetraethylene pentamine were added, refluxed at 90°C under a nitrogen atmosphere, stirred for 24 hours, repeatedly centrifuged and washed with anhydrous ethanol for 3 times, vacuum dried at 70°C, and ground and sieved to obtain a modified wear-resistant filler.
[0069] The preparation method of component B is as follows:
[0070] 32.5 parts by mass of the second polymer polyol, 6.5 parts by mass of the chain extender and 0.0003 parts by mass of the catalyst were mixed, vacuum dehydrated at 105°C and -0.1 MPa for 2.5 hours, cooled and poured into a ball mill for dispersion for 6 hours, discharged, sealed and set aside to obtain component B.
[0071] The preparation method of the second polymer polyol is as follows:
[0072] 4-ethynylbenzoic acid, polyether polyol, cyclohexane and concentrated sulfuric acid are mixed and shaken well, then zeolite is added and heated to reflux at 85°C for 2h, wherein the mass ratio of 4-ethynylbenzoic acid, cyclohexane and concentrated sulfuric acid is 3:3.5:1, and the molar ratio of the carboxyl group in 4-ethynylbenzoic acid to the hydroxyl group in the polyether polyol is 1:5, to obtain 4-ethynylbenzoic acid modified polyether polyol; a mixed solution of 2-ammonium iodide, bis(triphenylphosphine)palladium chloride, cuprous iodide, triphenylphosphine, acetonitrile and triethylamine is stirred and dissolved, and then 4-ethynylbenzoic acid modified polyether polyol is added, and nitrogen is added. The mixture was stirred and refluxed at 100°C for 17 hours under gas protection, poured into water, extracted with ethyl acetate, and the organic phase was washed with saturated brine and dried with anhydrous magnesium sulfate to obtain a second polymer polyol; wherein the mass ratio of 2-ammonium iodide, bis(triphenylphosphine)palladium chloride, cuprous iodide, triphenylphosphine, and 4-ethynylbenzoic acid modified polyether polyol was 1:0.05:0.05:0.05:1.2; the mass ratio of the mixed solution of 2-ammonium iodide, acetonitrile and triethylamine was 1:500; the volume ratio of acetonitrile and triethylamine in the mixed solution of acetonitrile and triethylamine was 5:1.
[0073] The preparation method of component A is as follows: 36.5 parts by mass of polyisocyanate and 38 parts of diluent are mixed, the temperature is raised to 75° C., 24.5 parts by mass of the first polymer polyol are added dropwise under stirring, the addition is completed within 40 minutes, the temperature is raised to 80° C., and the reaction is carried out at a constant temperature for 1.5 hours. At this time, the content of isocyanate groups is 6%, the temperature is lowered to 60° C., and vacuum degassing is carried out for 30 minutes to obtain component A.
[0074] Example 3
[0075] A method for preparing a wear-resistant vehicle body protective coating comprises the following preparation steps:
[0076] (1) The following raw material components and proportions are prepared: 100 parts by mass of component A, 88 parts by mass of component B, 8 parts by mass of modified wear-resistant filler, 23.5 parts by mass of pearlescent slurry, 17 parts by mass of solvent, 0.3 parts by mass of defoamer, 1.2 parts of leveling agent, and 1.6 parts by mass of anti-settling agent;
[0077] (2) 23.5 parts by weight of pearlescent slurry, 17 parts by weight of solvent, and 8 parts by weight of modified wear-resistant filler were mixed, heated to 150° C. and ball-milled for 4 h, then 88 parts by weight of component B were added, the temperature was further raised to 200° C., ball-milled for 6 h, and cooled to room temperature to obtain a primary mixture;
[0078] (3) Add 100 parts by weight of component A to the primary mixture, add 0.3 parts by weight of defoamer, 1.2 parts by weight of leveling agent, and 1.6 parts by weight of anti-settling agent after ball milling for 6 hours, continue ball milling for 3 hours, and let stand for 8 minutes to obtain a wear-resistant body protective coating.
[0079] The preparation method of the pearlescent slurry is as follows:
[0080] Under stirring at 400 rpm, 12 parts by mass of pearlescent pigment were added to 7 parts by mass of butyl acetate, followed by the addition of 1.5 parts by mass of acrylic dispersant and 3 parts by mass of butyl acetate, and stirring was continued for 40 minutes to obtain a pearlescent slurry.
[0081] The preparation method of the modified wear-resistant filler is as follows:
[0082] 10 parts by mass of copper-magnesium-aluminum hydrotalcite are added to 400 parts by mass of a hydrochloric acid solution with a concentration of 2 mol / L, refluxed at 80°C, stirred for 12 hours, repeatedly centrifuged and washed with water, dried at 70°C, ground and sieved, then added to 300 parts by mass of anhydrous ethanol, and then 40 parts by mass of silane coupling agent KH560 are added, refluxed at 90°C under a nitrogen atmosphere, stirred for 24 hours, repeatedly centrifuged and washed with anhydrous ethanol for 4 times, vacuum dried at 70°C, ground and sieved, continued to be added to 400 parts by mass of anhydrous ethanol, and then 30 parts by mass of tetraethylene pentamine were added, refluxed at 90°C under a nitrogen atmosphere, stirred for 24 hours, repeatedly centrifuged and washed with anhydrous ethanol for 4 times, vacuum dried at 70°C, and ground and sieved to obtain a modified wear-resistant filler.
[0083] The preparation method of component B is as follows:
[0084] 33 parts by mass of the second polymer polyol, 7 parts by mass of the chain extender and 0.0004 parts by mass of the catalyst were mixed, vacuum dehydrated at 110°C and -0.1 MPa for 2.5 hours, cooled and poured into a ball mill for dispersion for 6 hours, discharged, sealed and set aside to obtain component B.
[0085] The preparation method of the second polymer polyol is as follows:
[0086] 4-ethynylbenzoic acid, polyether polyol, cyclohexane and concentrated sulfuric acid were mixed and shaken well, then zeolite was added and heated to reflux at 85°C for 2.2h, wherein the mass ratio of 4-ethynylbenzoic acid, cyclohexane and concentrated sulfuric acid was 3:4:1, and the molar ratio of the carboxyl group in 4-ethynylbenzoic acid to the hydroxyl group in polyether polyol was 1:6, to obtain 4-ethynylbenzoic acid modified polyether polyol; 2-ammonium iodide, bis(triphenylphosphine)palladium chloride, cuprous iodide, triphenylphosphine, acetonitrile and triethylamine were stirred and dissolved, and then 4-ethynylbenzoic acid modified polyether polyol was added, and nitrogen The mixture was stirred and refluxed at 100°C for 18 hours under gas protection, poured into water, extracted with ethyl acetate, and the organic phase was washed with saturated brine and dried with anhydrous magnesium sulfate to obtain a second polymer polyol; wherein the mass ratio of 2-ammonium iodide, bis(triphenylphosphine)palladium chloride, cuprous iodide, triphenylphosphine, and 4-ethynylbenzoic acid modified polyether polyol was 1:0.05:0.05:0.05:1.3; the mass ratio of the mixed solution of 2-ammonium iodide, acetonitrile and triethylamine was 1:600; the volume ratio of acetonitrile and triethylamine in the mixed solution of acetonitrile and triethylamine was 5:1.
[0087] The preparation method of component A is as follows: 37 parts by mass of polyisocyanate and 39 parts of diluent are mixed, the temperature is raised to 75° C., 25 parts by mass of the first polymer polyol are added dropwise under stirring, the addition is completed within 40 minutes, the temperature is raised to 85° C., and the reaction is carried out at a constant temperature for 1.5 hours. At this time, the content of isocyanate groups is 7%, the temperature is lowered to 60° C., and vacuum degassing is carried out for 30 minutes to obtain component A.
[0088] Comparative Example 1
[0089] The difference between Comparative Example 1 and Example 2 is that only copper-magnesium-aluminum hydrotalcite is used as the wear-resistant filler to prepare the wear-resistant vehicle body protective coating; the other components, proportions and processes are the same as those of Example 2.
[0090] Comparative Example 2
[0091] The difference between Comparative Example 2 and Example 2 is that only nano calcium carbonate is used as the wear-resistant filler to prepare the wear-resistant vehicle body protective coating; the other components, proportions and processes are the same as those of Example 2.
[0092] Comparative Example 3
[0093] The difference between Comparative Example 3 and Example 2 is that the modified wear-resistant filler is obtained by modifying nano calcium carbonate with silane coupling agent KH560 and tetraethylenepentamine in sequence; the other components, proportions and processes are the same as those in Example 2.
[0094] Comparative Example 4
[0095] The difference between Comparative Example 4 and Example 2 is that the second polymer polyol only uses polyether polyol; the other components, proportions and processes are the same as those of Example 2.
[0096] Comparative Example 5
[0097] The only difference between Comparative Example 5 and Example 2 is that when preparing the wear-resistant car body protective coating, component A and component B are first mixed and ball-milled, and then modified wear-resistant filler, pearlescent slurry, solvent, defoaming agent, leveling agent and anti-settling agent are added and ball-milled to disperse; the remaining components, proportions and processes are the same as those in Example 2.
[0098] Effect example
[0099] Table 1 below shows the performance analysis results of the wear-resistant vehicle body protective coatings of Examples 1 to 5 of the present invention and Comparative Example 1.
[0100] Table 1
[0101] Adhesion / Grade Pencil hardness Flexibility / mm Neutral salt spray resistance Example 1 0 H 1 228h Rust Example 2 0 H 1 238h Rust Example 3 0 H 1 236h Rust Comparative Example 1 1 4B 5 116h Rust Comparative Example 2 1 2B 6 125h rust Comparative Example 3 0 2B 1 220h rust Comparative Example 4 1 HB 1 89h Rust Comparative Example 5 1 H 2 132h Rust
[0102] From the comparison of the experimental data of Examples 1 to 3 and Comparative Example 1 in Table 1, it can be found that the wear-resistant body protective coating prepared in the examples has good mechanical properties, adhesion properties, and corrosion resistance, and the coating film hardness is high; from the comparison of the experimental data of Example 2 and Comparative Examples 1 to 3, it can be found that the modified wear-resistant filler is modified by silane coupling agent KH560 and tetraethylenepentamine to obtain copper-magnesium-aluminum hydrotalcite, and the mechanical properties, adhesion properties, and corrosion resistance of the prepared wear-resistant body protective coating are good, and the coating film hardness is high; from the comparison of the experimental data of Example 2 and Comparative Example 4, it can be found that the second polymer polyol adopts 2-ethynylaniline modified polyether polyol, and the wear-resistant body protective coating prepared has good adhesion and corrosion resistance, and the coating film hardness is high; from the comparison of the experimental data of Example 2 and Comparative Example 5, it can be found that the pearlescent slurry, the modified wear-resistant filler, and the component B are first subjected to high-temperature ball milling, and the wear-resistant body protective coating prepared has good adhesion and corrosion resistance, and the coating film hardness is high.
[0103] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.
Claims
1. A wear-resistant car body protective coating, characterized in that: The raw material components include, by weight, 100 parts by weight of component A, 87-88 parts by weight of component B, 6-8 parts by weight of modified wear-resistant filler, 23.5 parts by weight of pearlescent slurry, 15-17 parts by weight of solvent, 0.2-0.3 parts by weight of defoamer, 0.8-1.2 parts by weight of leveling agent, and 1.4-1.6 parts by weight of anti-settling agent; the component A includes, by weight, 36-37 parts by weight of polyisocyanate, 24-25 parts by weight of first polymer polyol, and 37-39 parts by weight of diluent; the component B includes, by weight, 32-33 parts by weight of second polymer polyol, 6-7 parts by weight of chain extender, and 0.0002-0.0004 parts by weight of catalyst; The modified wear-resistant filler is obtained by sequentially modifying copper-magnesium-aluminum hydrotalcite with silane coupling agent KH560 and tetraethylenepentamine; the pearlescent slurry comprises 10 parts by weight of butyl acetate, 12 parts by weight of pearlescent powder pigment, and 1.5 parts by weight of acrylic dispersant; The second polymer polyol adopts 2-ethynylaniline modified polyether polyol; the preparation method of the second polymer polyol is as follows: 4-ethynylbenzoic acid, polyether polyol, cyclohexane and concentrated sulfuric acid are mixed and shaken, then zeolite is added and heated to reflux at 85°C for 1.8-2.2h, wherein the mass ratio of 4-ethynylbenzoic acid, cyclohexane and concentrated sulfuric acid is 3:3-4:1, and the molar ratio of the carboxyl group in 4-ethynylbenzoic acid to the hydroxyl group in the polyether polyol is 1:4-6, to obtain 4-ethynylbenzoic acid modified polyether polyol; a mixed solution of 2-iodoaniline, bis(triphenylphosphine)palladium chloride, cuprous iodide, triphenylphosphine, acetonitrile and triethylamine is stirred and dissolved, and then 4-ethynylbenzoic acid modified polyether polyol is added, and nitrogen is kept The mixture was stirred and refluxed at 100°C for 16-18h under protection, poured into water, extracted with ethyl acetate, and the organic phase was washed with saturated brine and dried over anhydrous magnesium sulfate to obtain a second polymer polyol; wherein the mass ratio of 2-iodoaniline, bis(triphenylphosphine)palladium chloride, cuprous iodide, triphenylphosphine, and 4-ethynylbenzoic acid modified polyether polyol was 1:0.05:0.05:0.05:1.1-1.3; the mass ratio of the mixed solution of 2-iodoaniline, acetonitrile and triethylamine was 1:400-600; the volume ratio of acetonitrile and triethylamine in the mixed solution of acetonitrile and triethylamine was 5:
1.
2. A method for preparing a wear-resistant vehicle body protective coating, characterized in that: The method comprises the following preparation steps: (1) Mixing the raw materials according to the raw material components and proportions of claim 1; (2) 23.5 parts by weight of pearlescent slurry, 15-17 parts by weight of solvent, and 6-8 parts by weight of modified wear-resistant filler were mixed, heated to 150°C and ball-milled for 4 hours, then 87-88 parts by weight of component B were added, the temperature was continued to be raised to 180-200°C, ball-milled for 6 hours, and cooled to room temperature to obtain a primary mixture; (3) Add 100 parts by mass of component A to the primary mixture, and after ball milling for 6 hours, add 0.2-0.3 parts by mass of defoamer, 0.8-1.2 parts by mass of leveling agent, and 1.4-1.6 parts by mass of anti-settling agent. Continue ball milling for 1-3 hours, and let it stand for 8 minutes to obtain a wear-resistant car body protective coating.
3. The method for preparing the wear-resistant vehicle body protective coating according to claim 2, characterized in that: The preparation method of the pearlescent slurry is as follows: Under stirring at 200-400 rpm, 12 parts by mass of pearlescent pigment were added to 7 parts by mass of butyl acetate, followed by adding 1.5 parts by mass of acrylic dispersant and 3 parts by mass of butyl acetate, and stirring was continued for 20-40 minutes to obtain a pearlescent slurry.
4. The method for preparing the wear-resistant vehicle body protective coating according to claim 2, characterized in that: The preparation method of the modified wear-resistant filler is as follows: 10 parts by mass of copper-magnesium-aluminum hydrotalcite are added to 400 parts by mass of a hydrochloric acid solution with a concentration of 2 mol / L, refluxed at 80°C, stirred for 12 hours, repeatedly centrifuged and washed with water, dried at 70°C, ground and sieved, then added to 300 parts by mass of anhydrous ethanol, and then 30-40 parts by mass of silane coupling agent KH560 are added, refluxed at 90°C under a nitrogen atmosphere, stirred for 24 hours, repeatedly centrifuged and washed with anhydrous ethanol for 2-4 times, vacuum dried at 70°C, ground and sieved, continued to be added to 400 parts by mass of anhydrous ethanol, and then 20-30 parts by mass of tetraethylene pentamine are added, refluxed at 90°C under a nitrogen atmosphere, stirred for 24 hours, repeatedly centrifuged and washed with anhydrous ethanol for 2-4 times, vacuum dried at 70°C, and ground and sieved to obtain a modified wear-resistant filler.
5. The method for preparing the wear-resistant vehicle body protective coating according to claim 2, characterized in that: The preparation method of component B is as follows: Mix 32-33 parts by mass of the second polymer polyol, 6-7 parts by mass of the chain extender, and 0.0002-0.0004 parts by mass of the catalyst, dehydrate under vacuum at 100-110°C and -0.1 MPa for 2-3 hours, cool and pour into a ball mill for dispersion for 6 hours, discharge, and seal for standby use to obtain component B.
6. The method for preparing the wear-resistant vehicle body protective coating according to claim 2, characterized in that: The preparation method of component A is as follows: 36-37 parts by mass of polyisocyanate and 37-39 parts of diluent are mixed, the temperature is raised to 75° C., 24-25 parts by mass of the first polymer polyol are added dropwise under stirring, the addition is completed within 40 minutes, the temperature is raised to 75-85° C., and the reaction is carried out at a constant temperature for 1.5 hours. At this time, the content of isocyanate groups is 6%-7%, the temperature is lowered to 60° C., and vacuum degassing is carried out for 30 minutes to obtain component A.
Citation Information
Patent Citations
Underwater anti-impact coating with rapid curing function
CN107523205A
Nanometer polyurethane flame-retardant waterproof coating and a preparing method thereof
CN108997924A